Challenges of treatment adherence with direct oral anticoagulants in pandemic. Issue 1 (February 2021) - Dittrich, Tolga; Polymeris, Alexandros; De Marchis, Gian Marco
Abstract : Purpose of review: Direct oral anticoagulants (DOAC) are crucial for the prevention of thromboembolic events in patients with nonvalvular atrial fibrillation. Drug adherence by the patient but also adherence to guidelines by the physician are suboptimal. This review highlights aspects of DOAC treatment during the coronavirus disease 2019 (COVID-19) pandemic and selected challenging scenarios. Recent findings: For patients with a newly diagnosed indication for oral anticoagulation, a new interim clinical guidance recommends starting DOAC instead of vitamin K antagonists if DOAC are not contraindicated. The goal is to reduce the potential exposure of patients to severe acute respiratory syndrome coronavirus during the routine coagulation monitoring visits. As COVID-19 can lead to kidney failure, we discuss the challenges of DOAC dosing in kidney failures. Finally, we discuss two common challenges – when to start a DOAC after an ischemic stroke linked to atrial fibrillation, and whether cerebral microbleeds, including their count, are per se a contraindication to DOAC. Summary: There are still open challenges regarding DOAC treatment on the patient and physician side, both related and unrelated to the pandemic.